Zmienność biochemiczna gleb siedlisk leśnych na granicy zasięgu buka zwyczajnego Fagus sylvatica L. w Polsce - Olszowska, Grażyna (Leśne Prace Badawcze, 2011)
The aim of this study was to determine the biochemical properties and enzymatic activity of forest soils at the leading range edge of European beech. Study sites were selected at the north-eastern range edge of beech in Poland. Research was conducted in fresh broadleaved forest habitat (6 plots), fresh mixed broadleaved forest (1 plot) and upland fresh broadleaved forest (1 plot). The dominant species in the stands studied was European beech (Fagus sylvatica L.) along with a small amount of oak. The soils in the plots studied were classified as acid brown, lessive brown and rusty brown soils. Soil samples from 0–5 cm and 5–15 cm depth were analyzed to determine: the activity of urease, asparaginase, acid phosphatase, dehydrogenases and the content of organic carbon and total nitrogen, pH, base cations (Na + , K + , Ca 2 + and Mg 2 + ), exchangeable acidity (Hw), cation exchange capacity (CEC), and the degree of base saturation of the sorption complex (%V). There was a significant correlation between the studied enzymatic and chemical parameters. Based on those biochemical properties that reflect the richness of soil nutrients and soil biological activity, the forest soil fertility was formulated. This value was the highest in the plot Góra Śląska and Mrągowo and was the lowest in Kwidzyn, Jamy and Brzeziny. In all the plots studied, the enzyme activity was significantly higher in the 0–5 cm layer than in the 5–15 cm layer : in the two respective layers enzyme activities were, urease 22.9 and 9.5; asparaginase 3.5 and 1.9; dehydrogenase 1.95 and 0.47, and acid phosphatase 0.89 and 0.22. The upper layer contained much more organic carbon, which is the substrate need for growth of soil microbes. All of the chemical parameters examined were higher in the 0–5 cm layer than at 5–15 cm. Soils in beech stands typically had high spatial variability in their chemical and biochemical properties. Soil fertility ratio can be applied in a detailed diagnosis of the status of forest habitats and it may complement other diagnostic tools used in chemical research of forest soils.